Construction of core-shell hybrid nanoparticles templated by virus-like particles. Issue 89 (14th December 2017) - Liu, A.; Yang, L.; Verwegen, M.; Reardon, D.; Cornelissen, J. J. L. M.
Abstract : Catalytically active gold in silica core–shell nanoparticles are prepared by pH controlled templating on virus-like particles. Abstract : Plant viruses have been widely used as templates for the synthesis of organic–inorganic hybrids. However, the fine-tuning of hybrid nanoparticle structures, especially the control of inorganic particle size as well as where the silication occurs ( i.e. outside and/or inside of the capsid), by simply tuning the pH remains a challenge. By taking advantage of the templating effect of Cowpea Chlorotic Mottle Virus (CCMV) protein cages, we show that the silication at the exterior or interior surface of protein capsids, as well as the resulting structures of silica/virus hybrid nanoparticles can be fine-tuned by pH. At pH 4.0, only small silica particles (diameter of 2.5 nm) were formed inside the protein cages; at pH 6.0, silication mainly takes place inside of the protein cages, leading to monodisperse silica nanoparticles with diameters of 14 nm; and at pH 7.5, silica deposition takes place both at the interior and exterior surfaces of protein cages in aqueous conditions. Under these reaction conditions, multiple component hybrid virus/nanoparticulate systems, such as CCMVAu/silica and Au/silica nanoparticles were prepared step-by-step. Upon removal of the CCMV template by thermal degradation a single gold nanoparticle can be encapsulated in a hollow silica shell emulating the structure of a baby's rattle with an unattached solid particle within a hollow particle. The Au/silica core-hollow shell nanoparticles can then be further used as a stable catalyst. It is anticipated that these synthetic methods provide a versatile methodology to prepare core–shell nanomaterials with well-designed structure and functionality.